Thermal spray coating, thermal spray powder, method for producing thermal spray powder, and method for producing thermal spray coating
By adding an appropriate amount of carbon, titanium or molybdenum to the rare earth fluoride spraying powder and adjusting its color, the problem of the sprayed coating being prone to discoloration and plasma resistance reduction after use is solved, achieving a longer service life and lower production costs.
Patent Information
- Application Number
- CN202211112737.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-03-01
- Filing Date
- 2018-02-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2038-02-28
AI Technical Summary
The existing rare earth fluoride spray coating is prone to discoloration due to the residue of resist decomposition and plasma etching after use, resulting in a decrease in plasma resistance and frequent cleaning, which affects long life.
By adding elements such as carbon, titanium or molybdenum to the rare earth fluoride spraying powder, the content is controlled between 0.01-2 mass % or 1-1000 ppm, and the color of the powder is adjusted by L*a*b* color representation, so that it is white, gray or black, thereby forming a spray coating that is not easy to discolor.
The color change of rare earth fluoride spray coating is achieved after use, reducing the cleaning frequency, extending the long life of the components, and reducing production costs.
Smart Images

Figure CN115354269B_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of February 28, 2018, an application number of 201880014710.6, and an invention name of "Spray coating, spray powder, method for manufacturing spray powder, and method for manufacturing spray coating". Technical Field
[0002] The present invention relates to a thermal spray coating containing a fluoride of a rare earth element, or a fluoride of the rare earth element and an oxyfluoride of a rare earth element, a thermal spray powder for obtaining the thermal spray coating, a method for producing the thermal spray powder, and a method for producing the thermal spray coating. Background Art
[0003] In recent years, since rare earth fluorides are relatively stable at high temperatures, in order to achieve the reduction of initial particles and the extension of the life of components by using rare earth fluorides in plasma-resistant components, components with rare earth fluoride spray coatings have been developed, such as components for plasma etching devices using halogen gas.
[0004] However, yttrium fluoride, which is a representative of rare earth fluorides, is usually white, so for plasma etching device components using halogen gas, after use, the residue of resist decomposition products adheres, resulting in a portion that changes color to brown. In addition, due to the influence of plasma etching, a phenomenon of partial color change from white to black occurs (Hall defect caused by color center, etc.), so this portion is cleaned intensively, resulting in the following problem: originally having plasma resistance and being able to extend the life, but the life is reduced by cleaning. It should be noted that as prior art documents, the following patent documents 1 to 6 can be cited.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-100039
[0008] Patent Document 2: Japanese Patent Application Publication No. 2012-238894
[0009] Patent Document 3: Japanese Patent No. 3894313
[0010] Patent Document 4: Japanese Patent Application Publication No. 2014-010638
[0011] Patent Document 5: Japanese Patent No. 5396672
[0012] Patent Document 6: Japanese Patent Application Publication No. 2016-079258 Summary of the invention
[0013] Problems to be solved by the invention
[0014] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a thermal spray coating with little color change of a thermal spray component after use, a thermal spray powder for obtaining the thermal spray coating, and a method for producing the thermal spray powder and the thermal spray coating.
[0015] Means for solving problems
[0016] The inventors of the present invention have conducted intensive research to achieve the above-mentioned purpose, and have completed the present invention as a result. That is, the above-mentioned problem is that rare earth fluorides and rare earth fluorides including oxyfluorides are basically white. From this point of view, in order to color these rare earth fluorides gray or black, it is considered to add other elements. However, for plasma-resistant components, since they are mainly used in semiconductor manufacturing processes, it is necessary to consider the point of anti-pollution, and it is also necessary to suppress the amount of addition. Therefore, it is required to use a small amount of added elements to form a sprayed coating of rare earth fluorides and rare earth fluorides including oxyfluorides in white, gray or even black with a specified chromaticity. Therefore, in view of this requirement, the research was continued, and it was found that, especially when containing carbon, or titanium or molybdenum, it is effective to contain 0.01 to 2 mass% in the case of carbon and 1 to 1000 ppm in the case of titanium and molybdenum. Further, for L * a * b * Various studies have been conducted on chromaticity expression, and it is known that by using L * a * b ** Chromaticity shows L * 25 or more but less than 91, sometimes 25 to 64, a * -3.0~+5.0, b * The present invention has been completed by using a spraying powder of a rare earth fluoride or a rare earth fluoride containing oxyfluoride having a temperature of -6.0 to +8.0, thereby obtaining a sprayed coating having a temperature of white, gray or even black that can achieve the purpose of the present invention.
[0017] Therefore, as a first invention, the following thermal spray coating, thermal spray powder, and a method for producing the thermal spray powder are provided.
[0018] [1] A thermal spray coating, characterized in that it is a thermal spray coating comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (5),
[0019] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0020] (2) Oxyfluorides of the above rare earth elements
[0021] (3) Oxides of the above rare earth elements
[0022] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0023] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0024] Contains 0.004 to 2 mass % of carbon or 1 to 1000 ppm of titanium or molybdenum, and
[0025] In the case where the above-mentioned oxyfluoride (2) is not contained, L * a * b * Chromaticity, L * 25~64, a * -3.0~+5.0, b * It is gray or even black from -6.0 to +8.0.
[0026] In the case of containing the above-mentioned oxyfluoride (2), L * a * b * Chromaticity, L * 25 or more and less than 91, a * -3.0~+5.0, b * It is white, gray or even black with a range of -6.0 to +8.0.
[0027] [2] The thermal spray coating of [1], wherein the rare earth element is one or more selected from Y, Gd, Yb, and La.
[0028] [3] The thermal sprayed coating of [1] or [2], wherein the oxygen content is 0.01 to 13.5 mass %.
[0029] [4] The thermal spray coating according to any one of [1] to [3], wherein the carbon content is 0.004 to 0.15 mass %.
[0030] [5] A powder for thermal spraying, characterized in that it is a powder for thermal spraying comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (6),
[0031] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0032] (2) Oxyfluorides of the above rare earth elements
[0033] (3) Oxides of the above rare earth elements
[0034] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0035] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0036] (6) Oxides of one or more metals selected from Al, Si, Zr, and In
[0037] Contains 0.004 to 2 mass % carbon or contains 1 to 1000 ppm titanium or molybdenum, and is used for L * a * b * Chromaticity, L * 25 or more and less than 91, a * -3.0~+5.0, b * It is white, gray or even black with a range of -6.0 to +8.0.
[0038] [6] The thermal spraying powder of [5], wherein the rare earth element is one or more selected from Y, Gd, Yb and La.
[0039] [7] The thermal spray powder of [5] or [6], wherein the oxygen content is 0.01 to 13.5 mass %.
[0040] [8] The thermal spray powder according to any one of [5] to [7], which is a fired thermal spray powder and has a carbon content of 0.004 to 0.15% by mass.
[0041] [9] The thermal spray powder according to any one of [5] to [7], which is an unfired thermal spray powder and has a carbon content of 0.004 to 1.5% by mass.
[0042]
[10] A method for producing a powder for thermal spraying, which is a method for producing a powder for thermal spraying according to any one of [5] to [8], characterized in that a white powder comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (6), and a slurry of a carbon source used in such a way that the carbon concentration of the powder for thermal spraying becomes 0.004 to 2 mass %, are dried, roasted, and sintered to obtain a powder for thermal spraying. * a * b * Chromaticity shows L * 25 or more and less than 91, a * -3.0~+5.0, b * It is white, gray or even black spray powder with a temperature of -6.0 to +8.0.
[0043] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0044] (2) Oxyfluorides of the above rare earth elements
[0045] (3) Oxides of the above rare earth elements
[0046] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0047] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0048] (6) Oxides of one or more metals selected from Al, Si, Zr, and In
[0049]
[11] A method for producing a thermal spraying powder according to
[10] , wherein the powder is calcined at 500 to 800°C in nitrogen and then fired at 800 to 1000°C in a vacuum or inert gas atmosphere.
[0050]
[12] A method for producing a powder for spraying according to
[10] or
[11] , wherein the oxygen content of the white powder comprising the above (1) and / or (2), or a mixture of the above (1) and / or (2) and one or more selected from the above (3) to (6) is 0.01 to 13.5% by mass.
[0051]
[13] The production method according to any one of
[10] to
[12] , wherein the carbon source is used so that the carbon concentration of the thermal spraying powder becomes 0.004 to 0.15 mass %.
[0052]
[14] A method for producing a spray powder, which is a method for producing a spray powder according to any one of [5] to [8], characterized in that a slurry comprising white powder (1) and / or (2) or a mixture of (1) and / or (2) and one or more selected from (3) to (6), polyvinyl alcohol, and a water-soluble salt of titanium or molybdenum used in such a manner that the concentration of titanium or molybdenum in the spray powder becomes 1 to 1000 ppm is granulated, dried, and calcined to obtain a spray powder. * a * b * Chromaticity shows L * 25 or more and less than 91, a * -3.0~+5.0, b * It is a white, gray or even black spray powder with a temperature of -6.0 to +8.0.
[0053] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0054] (2) Oxyfluorides of the above rare earth elements
[0055] (3) Oxides of the above rare earth elements
[0056] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0057] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0058] (6) Oxides of one or more metals selected from Al, Si, Zr, and In
[0059]
[15] A method for producing a thermal spraying powder according to
[14] , wherein the granulated and dried powder is sintered at 800 to 1000°C in a vacuum or inert gas atmosphere.
[0060]
[16] A method for producing a powder for spraying according to
[14] or
[15] , wherein the oxygen content of the white powder comprising the above (1) and / or (2), or a mixture of the above (1) and / or (2) and one or more selected from the above (3) to (6) is 0.01 to 13.5% by mass.
[0061] In addition, the inventors conducted further research and found that even if there is no carbon, titanium or molybdenum in the film, plasma light and reaction gas can be used to make the surface of the film gray or even black due to the color center. By pre-treating the film surface with plasma exposure to make it gray or even black, when the sprayed film is used as a component for a plasma etching device, no discoloration due to use will occur, thereby achieving the above-mentioned purpose of the present invention.
[0062] Therefore, as a second invention, the following thermal spray coating and a method for producing the thermal spray coating are provided.
[0063]
[17] A thermal spray coating, characterized in that it is a thermal spray coating comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (5), and having a thermal spray coating on the surface * a * b * Chromaticity shows L * 25~64, a * -3.0~+5.0, b * It is a gray or black layer with a gray or black color ranging from -6.0 to +8.0.
[0064] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0065] (2) Oxyfluorides of the above rare earth elements
[0066] (3) Oxides of the above rare earth elements
[0067] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0068] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0069]
[18]
[17] The thermal spray coating of claim 1, wherein the depth of the gray or black layer is within 2 μm from the coating surface.
[0070]
[19] The thermal sprayed coating of
[17] or
[18] , wherein the oxygen content is 0.01 to 13.5 mass %.
[0071]
[20] A method for producing a thermal spray coating according to any one of
[17] to
[19] , characterized in that a white powder comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (6) is thermally sprayed onto the surface of a substrate to obtain a thermal spray coating. * a * b * Chromaticity shows L * 81 or above, a * -3.0~+3.0, b * The thermal spray coating is a white thermal spray coating with a temperature of -3.0 to +3.0, and a plasma exposure treatment is performed on the thermal spray coating to form a L * a * b * Chromaticity shows L * 25~64, a * -3.0~+5.0, b * It is a gray or black layer with a gray or black color ranging from -6.0 to +8.0.
[0072] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0073] (2) Oxyfluorides of the above rare earth elements
[0074] (3) Oxides of the above rare earth elements
[0075] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0076] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0077] (6) Oxides of one or more metals selected from Al, Si, Zr, and In
[0078]
[21] A method for producing a thermal spray coating according to
[20] , wherein the depth of the gray or black layer is within 2 μm from the coating surface.
[0079]
[22] A method for producing a powder for spraying of
[20] or
[21] , wherein the oxygen content of the white powder comprising the above (1) and / or (2), or a mixture of the above (1) and / or (2) and one or more selected from the above (3) to (6) is 0.01 to 13.5% by mass.
[0080] Effects of the Invention
[0081] According to the present invention, since a spray coating of a rare earth fluoride containing a rare earth fluoride or an oxyfluoride in white, gray, or even black with a predetermined chromaticity can be formed by atmospheric plasma spraying, it is possible to reduce costs. In addition, when a component having the spray coating of the rare earth fluoride in white, gray, or even black with a predetermined chromaticity is used as a plasma-resistant component in a halogen gas, there is little change in partial color, and when it is taken out for cleaning, it is not necessary to partially perform difficult cleaning, so that the component can reliably achieve its original long life. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Figure 1 This is an explanatory diagram for explaining a method for measuring the thickness of the black layer of a thermal spray coating.
[0083] Figure 2 This is a graph showing the relationship between the carbon content and hardness of the thermal sprayed coating in the experimental example. DETAILED DESCRIPTION
[0084] The present invention is described in more detail below.
[0085] In the above-mentioned first invention, the thermal spray coating of the present invention is a thermal spray coating comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (5).
[0086] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0087] (2) Oxyfluorides of the above rare earth elements
[0088] (3) Oxides of the above rare earth elements
[0089] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0090] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0091] The thermal spraying powder of the present invention is a thermal spraying powder comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (6).
[0092] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0093] (2) Oxyfluorides of the above rare earth elements
[0094] (3) Oxides of the above rare earth elements
[0095] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0096] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0097] (6) Oxides of one or more metals selected from Al, Si, Zr, and In
[0098] In this case, as the above-mentioned rare earth element, as described above, one or more rare earth elements of Group 3A including yttrium (Y) can be used, and in particular, one or more heavy rare earth elements selected from Y, Gd, Yb and La are preferred. Among them, as the oxyfluoride of the rare earth element (2), oxyfluorides of various crystal structures can be used, for example, in the case of the oxyfluoride of Y, oxyfluorides of various crystal structures such as Y5O4F7, Y6O5F8, and YOF can be used.
[0099] The average particle size of the particles of the powder for thermal spraying in the present invention is preferably 1 to 100 μm. If the average particle size is less than 1 μm, it is possible to evaporate and scatter in the plasma flame during thermal spraying, resulting in a corresponding loss. On the other hand, if the average particle size exceeds 100 μm, it is possible that the particles are not completely melted in the plasma flame during thermal spraying and the like, and the melting is incomplete, and the particles become unmelted powder, which may cause a decrease in the adhesion strength. It should be noted that the above average particle size is the value of D50 of the particle size distribution measured by the laser diffraction method.
[0100] The thermal spray coating and thermal spray powder of the present invention contain rare earth fluoride powder (such as L * : 91 or above, a * :-3.0~+3.0, b * : -3.0 to +3.0 yttrium fluoride powder, etc.), rare earth fluoride powder containing oxyfluoride is given a gray or even black material to prepare L * 25 or more and less than 91, a * -3.0~+5.0, b * L is -6.0~+8.0 * a * b * However, regarding the above L * The value of L is L in the case of a film containing no oxyfluoride of the rare earth element (2) above. * :25~64。 As the material imparting gray or even black, for example, carbon, titanium, and molybdenum are used. In the case of carbon, it is preferred that the film or powder contain 0.004~2 mass %, especially 0.05~1.8 mass %, and in the case of titanium and molybdenum, it is preferred that the film or powder contain 1~1000ppm, especially 1~800ppm. In addition, in the present invention, there is no particular restriction on the oxygen content of the thermal spray film and the thermal spray powder, and it is preferably 0.01~13.5 mass %, and more preferably 0.05~8 mass %.
[0101] Here, according to the knowledge of the inventors, the above-mentioned carbon content sometimes affects the hardness of the film. If the carbon content increases, the hardness of the film sometimes decreases. Therefore, when a high film hardness is required, it is preferred to make the carbon content less than 0.15 mass%, especially less than 0.1 mass%. Furthermore, the lower limit of the carbon content is 0.004 mass%, preferably 0.01 mass%, and more preferably 0.02 mass%, as described above. A film having a hardness of more than 300 HV, especially more than 400 HV, can be obtained. When such a high hardness film is to be obtained, in the case of a fired spraying powder, the carbon content can be made 0.004 to 0.15 mass%, and in the case of an unfired spraying powder, the carbon content can be made 0.004 to 1.5 mass%. By spraying such a spraying powder, a sprayed film with a carbon content of less than 0.15 mass% and the above-mentioned good hardness can be obtained.
[0102] There is no particular limitation on the means for containing the carbon. For example, the following method can be used: a slurry is prepared using a solution containing a white powder consisting of the above (1) and / or (2), or a mixture of the above (1) and / or (2) and one or more selected from the above (3) to (6), and a carbon source, and the mixture is mixed for 5 to 60 minutes, dried, granulated, and calcined. In this case, as the carbon source, carbon, aliphatic hydrocarbons, aromatic hydrocarbons, etc. can be used. If necessary, they can be dissolved in water or an organic solvent and mixed. For example, a product obtained by diluting phenol with alcohol, a water-soluble organic substance (such as an acrylic binder, carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), sucrose) can be used. As long as it becomes a carbon source by calcining, it is not limited to this. As for the addition of carbon, direct mixing, impregnation, coating, spraying, etc. can be used. After the carbon source and the above powder are mixed and dried, it is preferably calcined at 500 to 1000°C in nitrogen. After calcination, the powder for spraying is sieved to obtain a white, gray or even black powder for spraying with the above-mentioned specified chromaticity. In addition, after the above-mentioned carbon source is mixed with the above-mentioned powder, dried and granulated, the mixed dry powder can be directly used as the powder for spraying without calcination. Furthermore, when a powder for spraying with a fine particle size (1 to 10 μm) is used as an SPS (suspension plasma spraying) slurry, drying and granulation are not required.
[0103] When obtaining the powder for spraying in this way, in the present invention, it is important to control the addition concentration of phenol, acrylic binder, CMC, PVA, sucrose, etc., which serve as a carbon source, so that the carbon concentration in the powder for spraying becomes 0.004-2 mass%. If the carbon content is less than 0.004 mass%, the target colored film cannot be obtained, the powder strength becomes weak during high-temperature firing and spraying, and sometimes uneven powder performance occurs. On the other hand, if the carbon content exceeds 2 mass%, the carbon concentration is too high and becomes a residual substance, which often causes contamination and a decrease in the hardness of the sprayed film. In addition, in order to form a film with a high hardness of, for example, 300 HV or more, especially 400 HV or more as described above, in the case of fired spraying powder, it is preferred to control the addition concentration of the carbon source so that the carbon content of the powder for spraying becomes 0.004-0.15 mass%, especially 0.01-0.1 mass%, and in the case of unfired spraying powder, it is preferred to control the addition concentration of the carbon source so that the carbon content becomes 0.004-1.5 mass%.
[0104] The method of containing titanium or molybdenum is not particularly limited, and the following method can be exemplified: a white powder consisting of the above (1) and / or (2), or a mixture of the above (1) and / or (2) and one or more selected from the above (3) to (6), polyvinyl alcohol (PVA), water, and a water-soluble salt of titanium or molybdenum such as titanium chloride, titanium ammonium, molybdenum chloride, and molybdenum ammonium are mixed to form a slurry, which is then granulated and dried using a spray dryer. Furthermore, the powder is fired at 800° C. to 1000° C. in a vacuum or inert gas atmosphere to obtain a gray or black thermal spray powder. In this case, the content of titanium or molybdenum is 1 to 1000 ppm. If the content of titanium or molybdenum is less than 1 ppm, the target colored film cannot be obtained. If the content of titanium or molybdenum is more than 1000 ppm, it may cause contamination, especially when used in a semiconductor manufacturing device.
[0105] The thermal spray coating of the present invention can be formed by, for example, spraying the thermal spray powder of the present invention onto a substrate such as a member of a plasma etching device to form a film. Here, as the substrate, there is no particular limitation, and metals, alloys, ceramics {metal nitrides, metal carbides, metal oxides (such as aluminum oxide, aluminum nitride, silicon nitride, silicon carbide, etc.)}, glass (quartz glass, etc.) and the like having Al, Fe, Si, Cr, Zn, Zr or Ni as the main component can be used.
[0106] The thickness of the spray coating of the present invention can be appropriately set according to the purpose, etc., and there is no particular limitation. In order to impart corrosion resistance, when the corrosion-resistant component of the plasma etching device is formed as a corrosion-resistant film, it is preferably 50 to 500 μm, and more preferably 150 to 300 μm. If the thickness of the film is less than 50 μm, it may need to be replaced due to very small corrosion. On the other hand, if the thickness of the film exceeds 500 μm, it is too thick and may become easy to peel off.
[0107] The spray coating of the present invention can be formed by spraying the spray powder of the present invention on the surface of the substrate by a suitable spraying method such as plasma spraying, reduced pressure plasma spraying, SPS spraying, etc. In this case, the plasma gas is not particularly limited, and nitrogen / hydrogen, argon / hydrogen, argon / helium, argon / nitrogen, argon / hydrogen / nitrogen, etc. can be used. It should be noted that there is no particular limitation on the spraying conditions, etc., and they can be appropriately set according to the specific materials of the substrate, the rare earth fluoride spray powder, etc., the purpose of the obtained spraying component, etc.
[0108] The thermal spray coating of the present invention thus obtained is as described above, in the case where the oxyfluoride of the rare earth element (2) is not contained, * a * b * Chromaticity shows L *25~64, a * -3.0~+5.0, b * In the case of the rare earth element oxyfluoride mentioned in (2), L * a * b * Chromaticity shows L * 25 or more and less than 91, preferably 25 to 85, more preferably 25 to 80, a * -3.0~+5.0, b * The range is -6.0 to +8.0, white, gray or even black. * a * b * The spray coating is white, gray or even black, which is clearly defined in the chromaticity expression, so that it is no longer necessary to perform difficult cleaning of the parts when the treated object is removed and cleaned, and the original long life of the component can be achieved. * a * b * The chromaticity can be measured in accordance with JIS Z 8729 using, for example, a colorimeter (CHOROMAMETER) CR-200 manufactured by Minolta.
[0109] In the thermal spray coating of the present invention, when a thermal spray powder containing only the rare earth element fluoride of (1) above, such as YF3 thermal spray powder, is thermally sprayed, a gray or even black thermal spray coating having a single crystal structure of YF3 is obtained. On the other hand, when a thermal spray powder obtained by mixing the rare earth element fluoride of (2) above, or the rare earth element oxide of (3) above with the rare earth element fluoride of (1) above, such as a thermal spray powder obtained by mixing Y oxyfluoride (Y5O4F7, Y6O5F8) and Y oxide (Y2O3) with YF3, is thermally sprayed, a white or gray or even black thermal spray coating having a predetermined chromaticity containing a multi-phase Y oxyfluoride crystal phase in addition to YF3, such as YF3+Y5O4F7, YF3+Y6O5F8, is obtained. Furthermore, when a spraying powder obtained by mixing the above-mentioned rare earth element fluoride (1) with the above-mentioned metal oxide (6), for example, a spraying powder obtained by mixing an Al-based oxide with YF3, is sprayed, YOF+Y3Al5O 12 +Y7O6F9, YF3+Y5O4F7+Y3Al5O 12 、Y6O5F8+Y3Al5O 12 A multi-phase thermal spray coating containing fluoride, oxyfluoride and YAG, etc. The crystal structure of such a thermal spray coating can be measured by X-ray diffraction.
[0110] In addition, as for the oxygen content of the spray coating and the spray powder, the oxygen content is determined by the oxygen content of the oxides of rare earth elements, oxyfluorides (such as Y2O3, Y5O4F7), etc. contained in the raw material powder. When the oxygen content in the spray coating is small, it has a YF3+Y5O4F7 crystal structure. If the oxygen content increases, it is transformed into a YF3+YOF crystal structure. If the oxygen content increases further, a Y2O3 crystal structure is sometimes observed in addition to YF3+YOF. These can be confirmed using XRD patterns. In the present invention, as described above, the oxygen content of the spray coating and the spray powder is preferably 0.01 to 13.5% by mass, more preferably 0.05 to 8% by mass, and further, when the oxygen content is less than 6% by mass, especially 2 to 4% by mass, it can provide a film with a hardness of more than 300 HV and excellent plasma resistance. * 25 or more and less than 91, a * -3.0~+5.0, b * It is a white, gray or even black spray coating with a temperature of -6.0 to +8.0.
[0111] However, when the thermal spray coating and thermal spray powder of the present invention do not contain the rare earth element oxyfluoride of (2), as described above, L * The upper limit of L is set to 64. * The value is set lower, thereby further achieving a longer life of the cleaning product. In addition, for the color of the spraying powder and the spraying film containing the oxyfluoride and oxide of the rare earth element mentioned above (2) and (3), the color value L can be controlled by the carbon content. * , so as long as L * The white value can be arbitrarily controlled to be less than 91. In this way, the thermal spraying powder and thermal spraying film of the present invention with a predetermined chromaticity of white, gray or even black can be provided.
[0112] Next, in the second invention, first, a white powder comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (6) is sprayed onto a substrate to form a L * a * b * Chromaticity shows L * 91 or above, a * -3.0~+3.0, b * It is a white spray coating with a temperature range of -3.0 to +3.0.
[0113] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0114] (2) Oxyfluorides of the above rare earth elements
[0115] (3) Oxides of the above rare earth elements
[0116] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0117] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0118] (6) Oxides of one or more metals selected from Al, Si, Zr, and In
[0119] Next, the thermal sprayed film is subjected to a plasma exposure treatment to form a L * a * b * Chromaticity shows L * 25~64, a * -3.0~+5.0, b * A gray or black layer having a gray or black color of -6.0 to +8.0. In this case, the depth (thickness) of the gray or black layer from the film surface is not particularly limited, but is preferably within 2 μm, particularly preferably about 1 μm.
[0120] The thermal spray coating thus obtained is characterized in that it is a thermal spray coating comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (5),
[0121] (1) Fluorides of one or more rare earth elements selected from the group consisting of rare earth elements of Group 3A including yttrium
[0122] (2) Oxyfluorides of the above rare earth elements
[0123] (3) Oxides of the above rare earth elements
[0124] (4) Composite oxides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0125] (5) Composite fluorides of the above rare earth elements and one or more metals selected from Al, Si, Zr, and In
[0126] On the surface with L * a * b * Chromaticity shows L * 25~64, a * -3.0~+5.0, b * It is a gray or black layer with a gray or black color ranging from -6.0 to +8.0.
[0127] As the above-mentioned plasma exposure treatment, as long as the surface of the film is gray or even blackened to the above-mentioned chromaticity by using plasma light and reaction gas, the frequency, output power of the plasma, the type, flow rate, gas pressure, etc. of the reaction gas can be appropriately set so as to obtain the above-mentioned chromaticity. Other matters are the same as those of the above-mentioned first invention. It should be noted that there is no particular limitation on the above-mentioned spraying powder used for spraying. For the same reasons as the above-mentioned first invention, the oxygen content is preferably 0.01 to 13.5% by mass, and more preferably 0.05 to 8% by mass.
[0128] Example
[0129] The present invention will be specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. In the following examples, % means mass %.
[0130] [Example 1]
[0131] 1 kg of ytterbium fluoride powder (average particle size 40 μm) with an oxygen concentration of 3.4% was added with 1 liter of phenol solution diluted with ethanol to 3%, mixed for 5 minutes, dried, and then calcined in a nitrogen stream at 800°C for 2 hours. -2 Torr or less) and fired at 1000°C for 2 hours to produce a powder for spraying. * a * b * Chromaticity L * :42.3、a * :-0.30, b * : -0.65 black, the carbon concentration in the powder is 1.3%. In addition, the oxygen concentration is 2.9%.
[0132] The thermal spray powder was used to deposit a film on an aluminum alloy member by plasma spraying using argon gas and hydrogen gas to form a film having a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :45.2、a * :-0.53, b * : -0.62, carbon concentration is 1.1%, and oxygen concentration is 3.6%.
[0133] The sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test device, and a plasma exposure test was performed using the conditions of a frequency of 13.56 MHz, a plasma output power of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. The color of the sprayed film taken out did not change.
[0134] [Comparative Example 1]
[0135] Ytterbium fluoride powder (average particle size 40 μm) was used and plasma sprayed using argon and hydrogen to form a film with a thickness of about 200 μm on an aluminum alloy member. * a * b * Chroma, the result is L * :91.46、a * :-0.47, b * : 0.75, carbon concentration is 0.003%.
[0136] The thermally sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test apparatus, and a plasma exposure test was conducted in the same manner as in Example 1 under the conditions of a frequency of 13.56 MHz, a plasma output of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. Partial discoloration to brown and black was observed in the thermally sprayed film taken out.
[0137] [Example 2]
[0138] Yttrium fluoride powder (average particle size 40 μm) with an oxygen concentration of 0.2% was immersed in a 30% sucrose aqueous solution, stirred for 10 minutes, filtered and dried. The yttrium fluoride powder was calcined with a nitrogen stream at 800°C for 2 hours, sieved with a #100 sieve, and a powder for spraying was obtained. The powder for spraying is L * a * b * Chromaticity L * :72.23、a * :-0.02, b * : Gray color of 3.12, the carbon concentration in the powder is 0.235% and the oxygen concentration is 0.75%.
[0139] The thermal spray powder was used to deposit a film on an aluminum alloy member by plasma spraying using argon gas and hydrogen gas to form a film having a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :76.18、a* :0.04, b * : 3.77, carbon concentration is 0.015%, and oxygen concentration is 1.1%.
[0140] The sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test device, and a plasma exposure test was performed using the conditions of a frequency of 13.56 MHz, a plasma output power of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. The color of the sprayed film taken out did not change.
[0141] [Example 3]
[0142] 4 liters of 2% aqueous solution of acrylic binder were added to 150 g of white yttrium oxide powder (average particle size 1.1 μm) and 850 g of yttrium fluoride powder (average particle size 3 μm) and mixed to prepare slurry, which was granulated and dried using a spray dryer and then sieved using a #100 sieve to prepare yttrium fluoride powder (average particle size 36 μm) to obtain powder for spraying. The powder for spraying was L * a * b * Chromaticity L * :88.46、a * :3.63, b * : -2.85 gray, the carbon concentration in the powder was 1.46%, and the oxygen concentration was 3.37%. In addition, X-ray diffraction of the powder was performed, and peaks of YF3 and Y2O3 were observed.
[0143] The thermal spray powder was used to deposit a film on an aluminum alloy member by plasma spraying using argon gas and hydrogen gas to form a film having a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :43.18、a * :0.87, b * : 3.78, carbon concentration was 0.068 mass %, and oxygen concentration was 3.73%. In addition, X-ray diffraction of the film was performed, and peaks of Y6O5F8, Y5O4F7, and Y2O3 were observed.
[0144] The sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test device, and a plasma exposure test was performed using the conditions of a frequency of 13.56 MHz, a plasma output power of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. The color of the sprayed film taken out did not change.
[0145] [Comparative Example 2]
[0146] Yttrium oxide powder (average particle size 40 μm) was used and plasma sprayed using argon and hydrogen to form a film with a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :92.75、a * :-0.23, b * : 0.73, carbon concentration is 0.002%.
[0147] The thermally sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test apparatus, and a plasma exposure test was conducted in the same manner as in Example 2 using the conditions of a frequency of 13.56 MHz, a plasma output of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. Partial discoloration to brown and black was observed in the thermally sprayed film taken out.
[0148] [Example 4]
[0149] 100 g of white yttrium oxide powder (average particle size 0.2 μm) and 900 g of yttrium fluoride powder (average particle size 3 μm) were mixed with 4 liters of a 1% aqueous solution of a carboxymethyl cellulose (CMC) binder to prepare a slurry, which was granulated and dried using a spray dryer. The powder was then calcined using a nitrogen stream at 800° C. for 2 hours and sieved using a #100 sieve to obtain yttrium fluoride powder (average particle size 37 μm) to obtain a powder for spraying. The powder for spraying was L * a * b * Chromaticity L * :58.46、a * :3.63, b * : 2.85 gray, the carbon concentration in the powder was 1.34%. In addition, the oxygen concentration was 2.0%. X-ray diffraction of the powder was performed, and peaks of YF3 and Y5O4F7 were observed.
[0150] The thermal spray powder was used to deposit a film on an aluminum alloy member by plasma spraying using argon gas and hydrogen gas to form a film having a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :37.78、a * :-0.06, b *: 5.76, carbon concentration was 0.098%. In addition, oxygen concentration was 3.26%. X-ray diffraction of the film was performed, and peaks of YF3 and Y5O4F7 were observed.
[0151] The sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test device, and a plasma exposure test was performed using the conditions of a frequency of 13.56 MHz, a plasma output power of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. The color of the sprayed film taken out did not change.
[0152] [Example 5]
[0153] 4 liters of 3% aqueous solution of acrylic binder were added to 100 g of white alumina powder (average particle size 3 μm) and 900 g of yttrium fluoride powder (average particle size 3 μm) and mixed to prepare slurry, which was granulated and dried using a spray dryer and then sieved using a #100 sieve to prepare yttrium fluoride powder (average particle size 30 μm) to obtain a powder for spraying with an oxygen concentration of 4.7%. The powder for spraying was L * a * b * Chromaticity L * :90.24、a * :4.60, b * : -5.55 white, the carbon concentration in the powder was 1.46%. In addition, X-ray diffraction of the powder was performed, and peaks of YF3 and Al2O3 were observed.
[0154] The thermal spray powder was used to deposit a film on an aluminum alloy member by plasma spraying using argon gas and hydrogen gas to form a film having a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :27.75、a * :2.96, b * : 0.64, carbon concentration was 0.13% by mass, and oxygen concentration was 4.9%. In addition, X-ray diffraction of the film was performed, and the results showed that Y6O5F8 and Y3Al5O 12 (YAG) peak.
[0155] The sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test device, and a plasma exposure test was performed using the conditions of a frequency of 13.56 MHz, a plasma output power of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. The color of the sprayed film taken out did not change.
[0156] [Example 6]
[0157] 4 liters of 0.2% aqueous solution of CMC binder were added to 50 g of white yttrium oxide powder (average particle size 0.2 μm), 50 g of white aluminum oxide powder (average particle size 3 μm) and 900 g of yttrium fluoride powder (average particle size 3 μm) to prepare slurry, which was granulated and dried by a spray dryer. The powder was calcined for 2 hours with a nitrogen stream at 1000°C and sieved with a #100 sieve to prepare yttrium fluoride powder (average particle size 30 μm). A powder for spraying with an oxygen concentration of 3.4% was obtained. The powder for spraying was L * a * b * Chromaticity L * :89.52、a * :-0.07, b * : 1.92 white, the carbon concentration in the powder is 0.004%. X-ray diffraction of the powder was performed, and the results showed that Y7O6F9+Y3Al5O 12 (YAG) peak.
[0158] The thermal spray powder was used to deposit a film on an aluminum alloy member by plasma spraying using argon gas and hydrogen gas to form a film having a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :89.75、a * :-0.23, b * : 0.73, carbon concentration was 0.009 mass%, and oxygen concentration was 3.8%. In addition, X-ray diffraction of the film was performed, and the results showed that Y6O5F8 and Y3Al5O 12 (YAG) peak.
[0159] The sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test device, and a plasma exposure test was performed using the conditions of a frequency of 13.56 MHz, a plasma output power of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. The color of the sprayed film taken out did not change.
[0160] [Comparative Example 3]
[0161] Yttrium fluoride powder (average particle size 30 μm) containing 3% oxygen was used and a film was attached to the aluminum alloy member by plasma spraying using argon and hydrogen to form a film with a thickness of about 200 μm. The L * a * b *Chroma, the result is L * :87.83、a * :-0.07, b * : 1.92, and the carbon concentration is less than 0.003%.
[0162] The thermally sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test apparatus, and a plasma exposure test was conducted in the same manner as in Example 3 using the conditions of a frequency of 13.56 MHz, a plasma output of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. Partial discoloration to brown and black was observed in the thermally sprayed film taken out.
[0163] [Example 7]
[0164] 1.5 liters of 3% aqueous solution of polyvinyl alcohol (PVA) and 1.5 g of titanium chloride (TiCl3) were added to 1 kg of yttrium fluoride powder with an oxygen concentration of 12.8%, and the mixture was mixed to form a slurry. The granulated powder was granulated and dried using a spray dryer to obtain a granulated powder. The granulated powder was calcined at 1000°C for 1 hour while flowing argon gas. The obtained powder for spraying was sieved with a #200 sieve to obtain a powder for spraying. The L * a * b * Chroma, the result is L * :38.21、a * :0.12, b * : 0.23 black powder, the titanium concentration in the powder is 680 ppm and the oxygen concentration is 13.1%.
[0165] The thermal spray powder was used to deposit a film on an aluminum alloy member by plasma thermal spraying using argon gas and hydrogen gas to form a film having a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :41.02、a * :-0.56, b * : 4.31. Furthermore, the titanium concentration of the film was 670 ppm, and the oxygen concentration was 13.5%.
[0166] The sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test device, and a plasma exposure test was performed using the conditions of a frequency of 13.56 MHz, a plasma output power of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. The color of the sprayed film taken out did not change.
[0167] [Example 8]
[0168] 1.5 liters of 2% aqueous solution of polyvinyl alcohol (PVA) and 2.0 g of molybdenum chloride (MoCl5) were added to 1 kg of yttrium fluoride powder with an oxygen concentration of 2%, and the mixture was mixed to form a slurry. The granulated powder was granulated and dried using a spray dryer to obtain a granulated powder. The granulated powder was calcined at 1000°C for 1 hour while flowing argon gas. The obtained powder for spraying was sieved with a #200 sieve to obtain a powder for spraying. The L * a * b * Chroma, the result is L * :45.23、a * :-0.08, b * : -0.21 black powder, the molybdenum concentration in the powder is 920 ppm. In addition, the oxygen concentration is 1.8%.
[0169] The thermal spray powder was used to deposit a film on an aluminum alloy member by plasma thermal spraying using argon gas and hydrogen gas to form a film having a thickness of about 200 μm. The L * a * b * Chroma, the result is L * :63.82、a * :-0.47, b * : 0.75. The molybdenum concentration of the film was 890 ppm, and the oxygen concentration was 2.5%.
[0170] The sprayed component and the silicon wafer coated with the resist were placed in a reactive ion plasma test device, and a plasma exposure test was performed using the conditions of a frequency of 13.56 MHz, a plasma output power of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr. The color of the sprayed film taken out did not change.
[0171] [Examples 9, 10, Comparative Examples 4, 5]
[0172] Granulated powders shown in Table 1 were prepared using gadolinium fluoride (average particle size 27.8 μm) with an oxygen concentration of 0.48% and lanthanum fluoride (average particle size 30.9 μm) with an oxygen concentration of 0.148%, and fired for 2 hours under the firing conditions shown in Table 1 to obtain a thermal spray powder having the carbon content, oxygen content, and chromaticity shown in Table 1. Next, the obtained thermal spray powder was used to form a thermal spray coating on the surface of an aluminum alloy member in the same manner as in Example 1 to obtain a thermal spray coating having the carbon content, oxygen content, and chromaticity shown in Table 1, and a plasma exposure test was performed in the same manner as in Example 1 to measure the chromaticity of the coating. The results are shown in Table 1.
[0173] [Table 1]
[0174]
[0175] As shown in Table 1, the reduction of carbon content was suppressed by performing sintering in an inert atmosphere (Examples 9 and 10), and the carbon content was maintained at 0.01% or more. On the other hand, when sintering was performed in the air (Comparative Examples 4 and 5), carbon was reduced to less than 0.01% due to oxidation, and the color of the film became white in the case of thermal spraying.
[0176] [Experimental example]
[0177] Using 100 g of white yttrium oxide (average particle size 0.2 μm) powder and 900 g of yttrium fluoride (average particle size 3 μm) powder, and CMC as a carbon source, seven types of spraying powders having different carbon concentrations as shown in Table 2 were obtained. In this case, the spraying powder of sample 6 was unfired powder prepared according to the method of Example 3, and the spraying powders of other samples were fired powder prepared according to the method of the above-mentioned Example 4. Next, each spraying powder was used to form a coating having a thickness of about 200 μm as shown in Table 2 on an aluminum alloy component. The surface hardness (HV) and cross-sectional hardness (HV) of each sprayed coating obtained were measured by the following method, and the relationship between the carbon content and the coating hardness was studied. The results are shown in Tables 2 and Figure 2 in the coordinate diagram.
[0178] (Method for measuring hardness)
[0179] For each component obtained, a 10 mm square test piece was produced by cutting. The surface and cross section were mirror finished (Ra = 0.1 μm), and the hardness of the film surface and cross section was measured using a Vickers hardness tester. The hardness was measured at a load of 300 gf and a load time of 10 seconds using a Vickers hardness tester (AVK-C1 manufactured by Akashi), and the surface hardness at 3 points and the cross section hardness at 3 points were measured, and the average values were evaluated.
[0180] [Table 2]
[0181]
[0182] As shown in Table 2 and Figure 2 As shown in , if the carbon content exceeds 0.15 mass %, the hardness of the film decreases, and if the carbon content is 0.15 mass % or less, especially 0.1 mass % or less, it is confirmed that a good film hardness exceeding 300 HV is obtained. Therefore, when high film hardness is required, it is preferred to make the carbon content 0.15 mass % or less, especially 0.1 mass % or less.
[0183] [Examples 11 to 14]
[0184] Using the powders of ytterbium fluoride, yttrium fluoride, and gadolinium fluoride shown in Table 3, the aluminum alloy member was plasma sprayed in the same manner as in Example 1 to form the sprayed coating shown in Table 3. The obtained sprayed coating was subjected to plasma exposure treatment under the conditions of a frequency of 13.56 MHz, a plasma output of 1000 W, a gas species of CF4+O2 (20 volume %), a flow rate of 50 sccm, and a gas pressure of 50 mtorr, to obtain a sprayed coating having the chromaticity shown in Table 3.
[0185] [Table 3]
[0186]
[0187] As shown in Table 3, a uniform black spray coating can be obtained by subjecting a common white rare earth fluoride spray coating to plasma exposure treatment using plasma light and etching gas. Furthermore, when a member having the black spray coating is used as a plasma-resistant member in a halogen gas, there is little partial color change, and it is not necessary to perform difficult cleaning on a part when removing and cleaning, and the original long life can be surely achieved.
[0188] The black spray coating obtained in Example 12 was ball-polished to form circular pits with a diameter of 1650 μm. Figure 1 The thickness of the black layer was measured and calculated using the calculation formula shown in , and the result was less than 2 μm, which was estimated to be about 1000 nm.
Claims
1. A spray coating, characterized in that: A thermal spray coating comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (5), (1) fluorides of one or more rare earth elements selected from the group consisting of Y, Gd, Yb and La; (2) Oxyfluorides of the rare earth elements; (3) oxides of the rare earth elements; (4) a composite oxide of the rare earth element and one or more metals selected from Al, Si, Zr, and In; (5) a composite fluoride of the rare earth element and one or more metals selected from Al, Si, Zr, and In, Contains 1 to 1000 ppm of titanium or molybdenum, and In the absence of the oxyfluoride of (2), L * a * b * Chromaticity, L * 25~64, a * -3.0~+5.0, b * It is gray or even black from -6.0 to +8.
0. In the case of containing the oxyfluoride of (2), L * a * b * Chromaticity, L * 25 or more and less than 91, a * -3.0~+5.0, b * It is white, gray or even black with a range of -6.0 to +8.
0. The oxygen content is 2 to 13.5 mass %.
2. Spraying powder, characterized in that: A powder for spraying comprising the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (6), (1) fluorides of one or more rare earth elements selected from the group consisting of Y, Gd, Yb and La; (2) Oxyfluorides of the rare earth elements; (3) oxides of the rare earth elements; (4) a composite oxide of the rare earth element and one or more metals selected from Al, Si, Zr, and In; (5) a composite fluoride of the rare earth element and one or more metals selected from Al, Si, Zr, and In; (6) oxides of one or more metals selected from Al, Si, Zr, and In, Contains 1 to 1000 ppm of titanium or molybdenum and is made of L * a * b * Chromaticity, L * 25 or more and less than 91, a * -3.0~+5.0, b * It is white, gray or even black with a range of -6.0 to +8.
0. The oxygen content is 2 to 13.5 mass %.
3. A method for producing a thermal spray powder, which is a method for producing a thermal spray powder according to claim 2, characterized in that: A slurry comprising white powder of the following (1) and / or (2), or a mixture of the following (1) and / or (2) and one or more selected from the following (3) to (6), polyvinyl alcohol, and a water-soluble salt of titanium or molybdenum used so that the concentration of titanium or molybdenum in the spraying powder is 1 to 1000 ppm is granulated, dried, and fired to obtain a spraying agent for L * a * b * Chromaticity shows L * 25 or more and less than 91, a * -3.0~+5.0, b * The powder for spraying is white, gray or even black with a temperature of -6.0 to +8.
0. (1) fluorides of one or more rare earth elements selected from the group consisting of Y, Gd, Yb and La; (2) Oxyfluorides of the rare earth elements; (3) oxides of the rare earth elements; (4) a composite oxide of the rare earth element and one or more metals selected from Al, Si, Zr, and In; (5) a composite fluoride of the rare earth element and one or more metals selected from Al, Si, Zr, and In; (6) oxides of one or more metals selected from Al, Si, Zr, and In, The white powder has an oxygen content of 2 to 13.5% by mass.
4. The method for producing a thermal spray powder according to claim 3, wherein: The granulated and dried powder is fired at 800 to 1000° C. in a vacuum or inert gas atmosphere.
Citation Information
Patent Citations
Formation method of pattern for lifttoff
JP1978096672A
Rare earth oxide thermal spraying member and powder for thermal spraying
JP2004100039A
Semiconductor device manufacturing method
JP2012238894A
Information retrieval system, information processing device, information retrieval method, and information retrieval program
JP2014010638A
Suppression method of tar stain in coke oven gas purification and composition therefor
JP2016079258A